Metalloproteinases TACE and MMP-9 Differentially Regulate Death Factors on Adult and Neonatal Monocytes After Infection with Escherichia coli - Stephan Dreschers (International Journal of Molecular Sciences, 2019)
Background: Cleaving ligands and receptors of the tumor necrosis factor (TNF) superfamily can critically regulate the induction of apoptosis. Matrix metalloproteinases (MMPs) such as MMP-9 and tumor necrosis factor-α-converting enzyme (TACE) have been shown to cleave CD95-Ligand (CD95L) and TNF/(TNF receptor-1) TNFR1 which induce phagocytosis induced cell death (PICD) in adult monocytes. This process is reduced in neonatal monocytes. Methods: Here we tested in vitro, whether Escherichia coli infection mounts for activation of MMP-9 and TACE in monocytes and whether this process regulates PICD. Results: The surface expression of TACE was most prominent on infected adult monocytes. In contrast, surface presentation of MMP-9 was highest on infected neonatal monocytes. Selective blocking of MMP-9 decreased CD95L secretion, while inhibition of TACE left CD95L secretion unaltered. Blocking of MMP-9 increased surface CD95L (memCD95L) expression on infected neonatal monocytes to levels comparable to infected adult monocytes. Moreover, MMP-9 inhibition raised PICD of infected neonatal monocytes to levels observed for infected adult monocytes. In contrast, TACE inhibition decreased PICD in infected monocytes. Addition of extracellular TNF effectively induced memCD95L presentation and PICD of adult monocytes and less of neonatal monocytes. Conclusion: MMP-9 activity is crucial for downregulating cell-contact dependent PICD in E. coli infected neonatal monocytes. By this mechanism, MMP-9 could contribute to reducing sustained inflammation in neonates.